AN OVERVIEW ON EARLY DETECTION OF CANCER: IMPORTANCE, EFFECTIVENESS, DETERMINENTS - EUN-WHAN LEE (International Journal of Pharma and Bio Sciences, 2026)
Today, non-communicable diseases (NCDs), mainly cancer represents a leading threat to human health and development. In the past few decades cancer was major killers in developed countries but now it is becoming a global issue with marked rise in mortality and morbidity in developing countries. Unlike developed countries the emergence of cancer epidemic in the developing countries has attracted less comment and little public health response although the developing countries contribute a great share to the global burden of cancer. In management or controlling cancer, early detection is very important. This review paper shows the current status of cancer in the world including low and middle income countries and then introduces importance of early detection of cancer, its evidences, effectiveness and several measures to manage cancer and early screening.